Renewable hydrogen production by a mild-temperature steam reforming of the model compound acetic acid derived from bio-oil - Li, Z.; Hu, Xun; Zhang, Lijun; Lu, G. (Elsevier Science, 2012)
In this study, steam reforming of acetic acid over Ni/La2O3 catalyst for hydrogen generation was investigated. The experiments were carried out by varying the reaction conditions such as Ni content, reaction temperature, liquid hourly space velocity (LHSV) and steam-to-carbon ratios (S/C), to evaluate the influences of these parameters on the steam reforming reactions for getting the best catalytic performances. The results showed that the Ni/La2O3 catalyst with the Ni loading of 20 wt.% presented the superior activity and selectivity. The reaction temperature, LHSV and S/C strongly influenced the reforming reactions. At T = 623 K, LHSV = 5.1 h−1 and S/C = 7.5:1, the catalyst exhibited the best performances, acetic acid was converted completely, and selectivity to hydrogen exceeded 93%. Moreover, the catalyst presented rather stable performances for the 100 h time-on-stream without any deactivation. Besides, the reaction pathways were also discussed, methyl species was the important intermediate in the reforming reactions, which was the precursors for the formation of the gaseous products, while hydroxyl species was another important intermediate that was important for the formation of hydrogen and elimination of the by-products.